Counseling and Christianity : Five Approaches - Greggo, Stephen P., 1956-; Sisemore, Timothy A. (Christian Association for Psychological Studies Books., 2012)
:What does authentic Christian counseling look like in practice? This volume explores how five major perspectives on the interface of Christianity and psychology would each actually be applied in a clinical setting. Respected experts associated with each of the perspectives depict how to assess, conceptualize, counsel and offer aftercare to Jake, a hypothetical client with a variety of complex issues. In each case the contributors seek to explain how theory can translate into real-life counseling scenarios. This book builds on the framework of Eric L. Johnson's Psychology Christianity: Five Views. These include the Levels-of-Explanation Approach, the Integration Approach, the Christian Psychology Approach, the Transformational Approach and the Biblical Counseling Approach. While Counseling and Christianity can be used independently of Johnson's volume, the two can also function as useful companions. Christians who counsel, both those in practice and those still in training, will be served by this volume as it strengthens the connections between theory and practice in relating our faith to the mental health disciplines. They will finally get an answer to their persistent but unanswered question: "What would that counseling view look like behind closed doors?" Christian Association for Psychological Studies (CAPS) Books explore how Christianity relates to mental health and behavioral sciences including psychology, counseling, social work, and marriage and family therapy in order to equip Christian clinicians to support the well-being of their clients." --